2014
DOI: 10.1007/s12975-014-0338-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Worsens Outcome After rt-PA Primarily in the Large-Vessel Occlusive Stroke Subtype

Abstract: Hyperglycemia at the time of ischemic stroke has been associated with poorer outcomes. Preclinical literature suggests that hyperglycemia is an independent prognostic factor and the vasculature is more vulnerable to reperfusion injury. We applied a method to match subjects on important baseline factors to test whether, independent of stroke severity, stroke subtype influences the effect of hyperglycemia on outcome after recombinant tissue plasminogen activator (rt-PA). We reanalyzed the NINDS rt-PA dataset wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…In a majority of the studies included in the present review, an admission random glucose or a FBG was carried out and included in the analysis of the outcomes. Stress hyperglycemia has been associated with poorer functional outcomes 15,17,40,70 and mortality 71 , irrespective of diabetes status after an acute ischemic stroke. However, more studies have found that stress hyperglycemia has been associated with infarct volume growth, early neurological deterioration (increase of ≥4 points on National Institute of Health Stroke Scale) 16 , poorer functional outcome 12,40,41,71,72 , higher mortality 32,43,46,53,73 and longer hospital stay 40 in people without a history of diabetes, including patients who underwent thrombolysis 71,[74][75][76] and mechanical thrombectomy 77 .…”
Section: Discussionmentioning
confidence: 99%
“…In a majority of the studies included in the present review, an admission random glucose or a FBG was carried out and included in the analysis of the outcomes. Stress hyperglycemia has been associated with poorer functional outcomes 15,17,40,70 and mortality 71 , irrespective of diabetes status after an acute ischemic stroke. However, more studies have found that stress hyperglycemia has been associated with infarct volume growth, early neurological deterioration (increase of ≥4 points on National Institute of Health Stroke Scale) 16 , poorer functional outcome 12,40,41,71,72 , higher mortality 32,43,46,53,73 and longer hospital stay 40 in people without a history of diabetes, including patients who underwent thrombolysis 71,[74][75][76] and mechanical thrombectomy 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and high blood glucose are well-known risk factors for ischemic stroke (5, 2729). While a number of ischemic studies showed worse outcomes with hyperglycaemia (7) others have shown protective effect of hyperglycaemia in small vessel disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…There are additional contributions from the patient’s age [24, 25] and whether the patient underwent recanalization therapy [1]. Baseline glucose is also highly associated with outcome, particularly when the patient has undergone recanalization [26], consistent between human and animal models [27]. Collaterals, some genetically determined, are also known to play a role in stroke outcomes in both humans and animals and can be altered by acquired conditions such as cardiovascular risk factors [2832].…”
Section: Ppredicts© As a Methods To Quantify Variabilitymentioning
confidence: 99%